2019
DOI: 10.1590/2179-8087.063717
|View full text |Cite
|
Sign up to set email alerts
|

Lauraceae Along an Altitudinal Gradient in Southern Brazil

Abstract: We performed a phytosociological study on an altitudinal gradient in Lauráceas State Park (Parque Estadual das Lauráceas/PR), aiming to describe the Montane Atlantic Rain Forest, to verify the importance of Lauraceae, and to evaluate the communities' successional stage. We distributed survey units (2,000 m² quadrats) along an altitudinal gradient and surveyed all individuals with DBH ≥ 10 cm, which composed the arboreal component. In smaller quadrats (250 m²), we surveyed regeneration individuals. The communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…H. alchorneoides, in turn, prepares the environment for S. guianensis, which, along with E. edulis and other shade-tolerant species, prepares the environment for more selective Lauraceae species, such as Ocotea catharinensis, Ocotea odorifera, and Cryptocarya spp. (Klein, 1980;Maçaneiro et al, 2015;Brotto et al, 2019). Klein (1980) observed that at this late successional stage − that is, when H. alchorneoides dominates and S. guianensis begins to appear − several Myrtaceae species join the community, a phenomenon we detected in the study area; this family had the second greatest number of species.…”
Section: Forest Structure and Compositionmentioning
confidence: 62%
See 2 more Smart Citations
“…H. alchorneoides, in turn, prepares the environment for S. guianensis, which, along with E. edulis and other shade-tolerant species, prepares the environment for more selective Lauraceae species, such as Ocotea catharinensis, Ocotea odorifera, and Cryptocarya spp. (Klein, 1980;Maçaneiro et al, 2015;Brotto et al, 2019). Klein (1980) observed that at this late successional stage − that is, when H. alchorneoides dominates and S. guianensis begins to appear − several Myrtaceae species join the community, a phenomenon we detected in the study area; this family had the second greatest number of species.…”
Section: Forest Structure and Compositionmentioning
confidence: 62%
“…Klein (1980) stated that O. catharinensis would often represent up to one-third or even half of the growing stock volume of pristine subtropical ERF stands. Accordingly, Brotto et al (2019) found that this species represents ~25% of the total stem volume of a montane ERF remnant within a protected area in the state of Paraná, southern Brazil.…”
Section: Forest Structure and Compositionmentioning
confidence: 99%
See 1 more Smart Citation